A multidisciplinary theoretical and methodological framework for the study of telephone interpreting. Issue 3 (2nd July 2020) - Iglesias Fernández, Emilia; Russo, Mariachiara
ABSTRACT: The complex nature of remote interpreting (RI) demands a multidisciplinary approach. The present article focuses on telephone interpreting (TI) in the light of the most relevant disciplines to suggest a coherent theoretical and methodologic framework. This approach will contribute to analysing TI components and mechanics, both for research purposes and for TI training. From the most general to the most fine-grained relevant paradigms, the authors will discuss the relevance of the following disciplines. The Ethnography of Communication will frame TI as a social activity. The sociology of Technologised Interaction will consider TI as the interaction between the social and the technical, where humans are constrained by the technical but also orient themselves towards the affordances offered by technology. In addition, Conversation Analysis will focus on talk as interaction. The role of Prosody and Phonetics in interpreter's positioning and agency and as a facilitator for a better coordination in turn-taking will also contribute to a more comprehensive approach to the study and training of TI. All these analytical paradigms need to be factored in when studying TI with a view to make RI trainees aware of the discursive mechanics - both linguistic and paralinguistic- and of their potential to become effective technologised communicators.